2013
DOI: 10.1021/pr400113n
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Fragmentation Conditions for iTRAQ-labeled Phosphopeptides

Abstract: Protein phosphorylation is an important post-translational modification that plays a regulatory role within numerous biological processes. The simultaneous identification, localization, and quantification of phosphorylated proteins is vital for understanding this dynamic control mechanism. The application of isobaric labeling strategies, for example, iTRAQ, for quantitative phosphopeptide analysis requires simultaneous monitoring of peptide backbone fragmentation, loss of phosphoryl moieties, and the cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…For data acquisition on the LTQ Orbitrap Velos, previously optimized MS/MS conditions for isobarically labeled phosphopeptides were used. [19] An observation made during this study (data not shown) was the increase in charge states of isobaric labeled peptides compared to non-labeled ones, as has been reported earlier. [18] To illustrate the benefit of using the multi-protease approach, each of the eight protein digests was analyzed separately after iTRAQ labeling (without prior phosphopeptide enrichment).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For data acquisition on the LTQ Orbitrap Velos, previously optimized MS/MS conditions for isobarically labeled phosphopeptides were used. [19] An observation made during this study (data not shown) was the increase in charge states of isobaric labeled peptides compared to non-labeled ones, as has been reported earlier. [18] To illustrate the benefit of using the multi-protease approach, each of the eight protein digests was analyzed separately after iTRAQ labeling (without prior phosphopeptide enrichment).…”
Section: Resultssupporting
confidence: 74%
“…To obtain quantitative information on the whole protein, rather than the phosphorylation sites only, fractions containing the non‐phosphorylated peptides (fractions: flow‐through and wash) were also analyzed by LC/ESI‐MS/MS. For data acquisition on the LTQ Orbitrap Velos, previously optimized MS/MS conditions for isobarically labeled phosphopeptides were used . An observation made during this study (data not shown) was the increase in charge states of isobaric labeled peptides compared to non‐labeled ones, as has been reported earlier …”
Section: Resultssupporting
confidence: 56%
“…Linke et al, found that high collision energy (CE) is required during HCD to optimize pY immonium ion signal 38 . For quantitative accuracy, we use an MS 3 based approach using CID-MS 2 for identification and HCD-MS 3 at high collision energy for quantification 3940 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, multi-stage activation which has shown improved identification rates for phospho-serine and phospho-threonine peptides 44 could be investigated for its utility for isobarically tagged phosphotyrosine peptides, but including the loss of 80 (HPO 3 ) which is not often included. As noted by Linke et al, optimal analysis of isobarically tagged phosphopeptides involves a balance between identification, localization and quantification 38 . They suggested a combined CID-MS 2 /HCD-MS 2 approach similar to the combined CID-MS 2 /HCD-MS 3 approach recommended here.…”
Section: Resultsmentioning
confidence: 99%
“… 105 The 2+ charged precursors are more sensitive to the applied normalized collision energy values than the 3+ charged precursor ions in HCD experiments. 106 Thingholm et al have shown that derivatization with isobaric mass tags significantly increases the average ion charge state of phosphopeptides compared to that of nonlabeled peptides, resulting in a considerable reduction in the number of identified phosphopeptides. 108 Interestingly, it was demonstrated that adding a perpendicular flow of ammonia vapor between the needle and the MS orifice in LC–MS/MS analyses reduced the average charge state of isobaric labeled peptides and resulted in an increase in peptide identification.…”
Section: Extended Applications Of Isobaric Labeling-based Quantificatmentioning
confidence: 99%